Ensino e vivência do handebol na educação física escolar : proposta baseada em jogos reduzidos - Rosa, Paulo Victor da (2024)
This study developed a teaching unit focused on teaching Handball, based on the use of Small-Sized Games in Physical Education classes in Elementary School II. The objective was to build a structured proposal that would offer theoretical and practical support for Physical Education teachers, providing a more meaningful and engaging teaching of Handball in Elementary School II. The proposal was implemented with students in the 6th grade of Elementary School, from the Municipal Elementary School 15 de Outubro, in Campos de Júlio, Mato Grosso. The research is considered a pedagogical intervention type, using a qualitative approach. The data collection instruments included two questionnaires: a diagnostic questionnaire, used to identify the experiences and expectations of students in relation to the thematic unit of sports, which allowed the planning of a teaching unit. At the end of this unit, a final questionnaire was applied to evaluate the impact on student learning and to obtain their opinions on the knowledge acquired about handball. In addition, a field diary was used to record observations during the process. The data collected were organized as proposed by Bogdan and Biklen (1994). A discussion of the results was held based on the construction of the teaching sequence with 20 classes, divided into 10 meetings of 2 hours. It was observed that the students were motivated to participate in the classes, going beyond the simple execution of skills, and had the opportunity to explore other types of knowledge, promoting comprehensive and collaborative learning. We conclude that the use of small-sided games in teaching sports proved to be an effective strategy to promote learning, favoring decision making, encouraging active participation of students and improving the understanding of the internal logic of handball. This pedagogical approach contributed to the development of autonomy and responsibility of students, allowing them to assume an active role in their own development process.